Differential Expression of Hypothalamic and Gill-crh System With Osmotic Stress in the Euryhaline Black Porgy, Acanthopagrus schlegelii - Aruna, Adimoolam; Wang, Tsan-Ping; Cao, Jyun-Cing; Lan, Dan-Suei; Nagarajan, Ganesan; Chang, Ching-Fong (Frontiers in Physiology, 2021)
The local gill production of corticotropin releasing hormone (crh) and crh-receptor (crhr) is hypothesized to play important roles during seawater (SW) and freshwater (FW) acclimation in euryhaline black porgy (Acanthopagrus schlegelii). The mRNA expression of crh, crhr and Na+/K+-ATPase (α-nka) was examined in SW and FW diencephalon (Dien) as well as in the gills at different exposure time by Q-PCR analysis. The in situ hybridization results indicate that crh mRNA hybridization signals were more abundant in FW fish in the gigantocellular (PMgc) and parvocellular (PMpc) part of the magnocellular preoptic nucleus versus SW fish. The crh and crhr-expressing cells were located in basal cells of gill filament. Furthermore, in vitro dexamethasone (DEX) treatment could increase the crh-system in the gill. Increased transcripts of the crh-system in the gill via in vitro and in vivo CRH treatments suggest that crh may regulate the system in a local manner. The a-Nka cells were localized in the filament and secondary lamellae mitochondria rich cells (MRCs) of FW fish at 8 hrs and one day. a-Nka cells were seen in both filament and lamellae in the FW but much less in SW fish indicating that gills play key roles in black porgy osmoregulation. Gill crh and crhr play important roles in the response to salinity stress.